Remote System, Does It Have an Impact on the Performance of Zoomers Employees? - Kairupan, Daniel Joel Immanuel (KINERJA, 2023)
The initial concept of a remote system (WFH) regulates flexible working hours, which can help employees determine work-life balance. The remote system gives employees the freedom to use their creativity to complete their tasks and responsibilities, which will greatly affect employee performance and work productivity. Central Statistics Agency (2020) shows data that the Zoomers generation is recorded as the generation that controls the next industry as active workers. The research method uses quantitative methods. This study uses the Smart-PLS 3.0 statistical tool with a sample of employees belonging to the Zoomers generation. Of the five hypotheses, three hypotheses were accepted, and two were rejected. The findings of this study can be an insight for businesspeople on whether the WFH pattern is still needed in increasing employees' productivity and performance.